Environmental conditions modulate the effect of epigenetic factors controlling the response of Arabidopsis thaliana to Plasmodiophora brassicae - Petitpas, Mathilde; Lapous, Romane; Le Duc, Mathieu; Lariagon, Christine; Lemoine, Jocelyne; Langrume, Christophe; Manzanares-Dauleux, Maria J.; Jubault, Mélanie (Frontiers in Plant Science, 2024)
The resistance of Arabidopsis thaliana to clubroot, a major disease of Brassicaceae caused by the obligate protist Plasmodiophora brassicae, is controlled in part by epigenetic factors. The detection of some of these epigenetic QTL (QTL epi ) has been shown to depend on experimental conditions. The aim of the present study was to assess whether and how temperature and/or soil water availability influenced both the detection and/or the extent of the effect of response QTL epi . The epiRIL population, derived from the cross between ddm1-2 and Col-0 (partially resistant and susceptible to clubroot, respectively), was phenotyped for response to P. brassicae under four abiotic conditions including standard conditions, a 5°C temperature increase, drought and flooding. The abiotic constraints tested had a significant impact on both the leaf growth of the epiRIL population and the outcome of the epiRIL/pathogen interaction. Linkage analysis led to the detection of a total of 31 QTL epi , 18 which were specific to one abiotic condition and 13 common to at least two environments. EpiRIL showed significant plasticity under epigenetic control which appeared to be specific to the traits evaluated and to the abiotic conditions. These results highlight that the environment can affect the epigenetic architecture of plant growth and immune responses and advance our understanding of the epigenetic factors underlying plasticity in response to climate change.